A combining technique based on channel shortening equalisation for ultra wideband cooperative systems. (17th January 2020) - Ouardas, Asma; Elahmar, Sid Ahmed
This paper presents a novel combining technique based on the channel shortening approach for cooperative diversity in the context of time hopping ultra wideband (TH-UWB) systems. Since UWB channel has very long impulse response, TH-UWB performances are affected by inter-symbol interference (ISI). Therefore, the use of the rake diversity combining is very effective, but it increases the receiver complexity due to its large number of correlations. The idea is to introduce a channel shortening equaliser (CSE) before the rake reception in first and second time slots at the relay and destination, respectively. The decode and forward (DF) is used as a relay protocol to retransmit signals and the relay is supposed equipped with multiple antennas and antenna selection criterion is used to exploit the diversity. Numerical results show that significant improvement in the BER is obtained by our proposed structure comparing to cases where the relay is equipped with a single antenna and multiple antennas (full diversity).